A Dialogue on Law and Social Protest - Gargarella, Roberto (2008)
This paper is about the regulation of the social protest. It is about how the law should react to the human rights violation and the social tensions. This discussion invites us to think about the theories of the democracy: it been analyzed the role of the social protests in the contemporary societies. Furthermore, it been said that in Latin America there is no sensibility with the interests of the disadvantaged groups that participates in the social protests. To the contrary, it been assumed that are criminal action that should be banned. The author show us arguments and counter arguments over this topic, mostly have a base on sentences of cases occurred in the United States and Argentina. In the one hand, the favorable arguments to the order idea and, in the other hand, the favorable ones to the protests. Regarding the arguments related with the order, we have: i) the law is violated by protests; ii)  when a protest happens there is conflict of rights, but who protests acts as if its right would be absolute; iii) the goals of the protesters are not genuine; iv) beside that, the ways by which the protest are realized are violent; v) the protesters should perform their right in a reasonable way, with time, place and way regulations; vi) the protests undermine the democracy. Now, to respond each argument, the arguments related with the protest are the next: i) what happens with the rights that allow the protest; ii) which is most important, the free pass o or the free speech?; iii) why the protests should be aseptic; iv) we should focus on the expressive component of the message and the public forum doctrine; v) the time, place and way regulations should not be used as excuses to undermine the political messages; in addition to the last, there are two principles that should be considered: the deliberative impartiality and the systematic violations; the last argument is about to ask ourselves vi) in what concept of democracy it been though. Finally, the author indicates that the notion of deliberative democracy does considered while judging the social protests yet. He emphasizes that it should be investigate more about where the deliberative theories take us when difficult social cases it been evaluated.